2020
DOI: 10.1002/hbm.25256
|View full text |Cite
|
Sign up to set email alerts
|

Parahippocampal area three gray matter is reduced in first‐episode schizophrenia spectrum: Discovery and replication samples

Abstract: Early course schizophrenia is associated with reduced gray matter. The specific structures affected first and how deficits impact symptoms and cognition remain unresolved. We used the Human Connectome Project multimodal parcellation (HCP‐MMP) to precisely identify cortical areas and investigate thickness abnormalities in discovery and replication samples of first‐episode schizophrenia spectrum individuals (FESz). In the discovery sample, T1w scans were acquired from 31 FESz and 31 matched healthy controls (HC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 87 publications
2
10
0
Order By: Relevance
“…In other regions such as the insular or cingulate cortex, gray matter loss in CHR-T has also been reported to exceed that of CHR_NT [ 75 ]. The structural alterations reported in previous studies are in line with the identified regions in the current analysis, such as temporal regions [ 76 ]; frontal cortex [ 77 79 ]; thalamus [ 72 ]; insula [ 80 ]; hippocampus and caudate nucleus [ 81 , 82 ]; pallidum, putamen [ 83 ]; parahippocampus [ 83 , 84 ]; and lingual cortex [ 85 ]. White matter: There is accumulating evidence of compromised white matter function leading to abnormalities in synchronization and connectivity in patients with schizophrenia [ 86 ], the most widely used measure being fractional anisotropy (FA) assessed with diffusion tensor imaging (DTI).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In other regions such as the insular or cingulate cortex, gray matter loss in CHR-T has also been reported to exceed that of CHR_NT [ 75 ]. The structural alterations reported in previous studies are in line with the identified regions in the current analysis, such as temporal regions [ 76 ]; frontal cortex [ 77 79 ]; thalamus [ 72 ]; insula [ 80 ]; hippocampus and caudate nucleus [ 81 , 82 ]; pallidum, putamen [ 83 ]; parahippocampus [ 83 , 84 ]; and lingual cortex [ 85 ]. White matter: There is accumulating evidence of compromised white matter function leading to abnormalities in synchronization and connectivity in patients with schizophrenia [ 86 ], the most widely used measure being fractional anisotropy (FA) assessed with diffusion tensor imaging (DTI).…”
Section: Discussionsupporting
confidence: 87%
“…In other regions such as the insular or cingulate cortex, gray matter loss in CHR-T has also been reported to exceed that of CHR_NT [ 75 ]. The structural alterations reported in previous studies are in line with the identified regions in the current analysis, such as temporal regions [ 76 ]; frontal cortex [ 77 79 ]; thalamus [ 72 ]; insula [ 80 ]; hippocampus and caudate nucleus [ 81 , 82 ]; pallidum, putamen [ 83 ]; parahippocampus [ 83 , 84 ]; and lingual cortex [ 85 ].…”
Section: Discussionsupporting
confidence: 87%
“…Further analysis based on ROI showed that these areas of AVH patients have higher CBF and lower FCS than HC ( Supplementary Figure 8 ). Many structural ( Onitsuka et al, 2004 ; Cui et al, 2018 ; Curtis et al, 2021 ), functional neuroimaging ( Allen et al, 2008 ), and circuit studies ( Benetti et al, 2015 ; Huang et al, 2019 ; Ren et al, 2021 ) have indicated that the left STG, particularly the primary and association auditory cortex, and the left MTG, play a key role in the etiology of AVHs. The STG on the left mainly deals with the perception of “speech,” that is, understanding the phonetic and semantic features of the speech content ( Modinos et al, 2013 ) and auditory feedback processing originating from the cerebellum ( Christoffels et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, both the PHG and ITG regions have been reported to have less gray matter volume in SZ patients than in HCs (Curtis et al, 2021;Zhuo et al, 2017). According to (Curtis et al, 2021), the thinner gray matter in the PHG of first episode SZ patients correlates with their hallucinations, processing speed, working memory, and verbal learning. Functionally, (Diederen et al, 2010) showed that auditory verbal hallucinations in SZ patients are consistently preceded by deactivation of the PHG.…”
Section: Cognitive Performance Is Related To the Ec Profile Of Sz Pat...mentioning
confidence: 99%
“…The third contributing variable to the connection-cognition CCA model was the effective connection from PHG to ITG, in the COG network. Structurally, both the PHG and ITG regions have been reported to have less gray matter volume in SZ patients than in HCs (Curtis et al, 2021;Zhuo et al, 2017). According to (Curtis et al, 2021), the thinner gray matter in the PHG of first episode SZ patients correlates with their hallucinations, processing speed, working memory, and verbal learning.…”
Section: Cognitive Performance Is Related To the Ec Profile Of Sz Pat...mentioning
confidence: 99%